Data and applications security and privacy XXXII : 32nd Annual IFIP WG 11.3 Conference, DBSec 2018, Bergamo, Italy, July 16-18, 2018, Proceedings /: 32nd Annual IFIP WG 11.3 Conference, DBSec 2018, Bergamo, Italy, July 16-18, 2018, Proceedings. (2018) - Unknown
No abstract available